Pengaruh Bonita dan Ketinggian Tempat Tumbuh terhadap Produktivitas Getah Pinus (Pinus merkusii) DI BKPH Purworejo, KPH Kedu Selatan - Erika Novita Andriani; Siman Suwadji (Jurnal Wana Tropika, 2026)
The Pine tree (Pinus merkusii Jungh. Et de Vriese) is one of the pioneer plant species that can grow in various conditions without requiring specific growing conditions, and the main product of this tree is Pine resin. This study aims to determine the effect of diameter at breast height (DBH) and altitude on Pine resin productivity, conducted at RPH Bruno plots 46 K-2 and 47B; RPH Katerban plots 103A and 105, BKPH Purworejo, KPH Kedu Selatan. Observations were carried out for 30 days with 3 data collection sessions on tapping wounds made by the researcher. The methods used were Quantitative and Qualitative with multiple linear regression analysis, with the multiple linear regression equation Y = 16.823 – 2.694 X1 – 0.006 X2; based on the regression equation, the value for DBH is -2.694 and for altitude is -0.006.  The results of this study show that Bonita and The altitude of the growing location affect Pine resin productivity. In addition, the analysis data of the correlation coefficient (R) in the coefficient of determination (R2) obtained a value of 1, meaning that the variables Bonita and the altitude of the growing location are strongly correlated with pine resin productivity. The estimated annual production results (year 2025) obtained by the researcher are lower compared to the RTT 2025 production target of BKPH Purworejo in the same plot. This result is due to the researcher only weighing resin from one tap made by the researcher, whereas in reality, tapping farmers make an average of two taps.